THE ETHICAL LANDSCAPE OF GUIDANCE AND COUNSELING SERVICES: PHILOSOPHICAL FOUNDATIONS, IMPLEMENTATION, AND CHALLENGES IN THE DIGITAL ERA - Irawan, Tb. Moh. Irma Ari; Solehuddin, M; Suryahadikusumah, Ahmad Rofi; Asiedu, Alice (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Ethical codes form the foundation of counseling professionalism, protecting clients and maintaining professional integrity. The digital era presents complex ethical challenges regarding data confidentiality, counsellors’ digital competence, and professional boundaries in virtual spaces. This study comprehensively explores the philosophical foundations, structure, implementation, and challenges of ethical codes for guidance and counseling in national and international contexts, identifying regulatory gaps in the digital era. This research employed a narrative literature review approach examining publications from 2015-2025 sourced from Scopus, Google Scholar, ERIC, PubMed, PsycINFO, and national journal portals. Analysis was conducted through thematic content analysis, encompassing systematic information extraction, thematic categorization, comparative analysis of Indonesian and international ethical codes, narrative synthesis, and critical interpretation of theoretical and practical implications. Results of this research indicate that ethical codes are rooted in philosophical foundations (ontology, epistemology, axiology) with universal principles: autonomy, beneficence, non-maleficence, justice, fidelity, and veracity. International comparison reveals ACA and ASCA (US) emphasize client protection and digital technology; BACP (UK) focuses on values-based practice; PACFA and ACA Australia prioritize cultural diversity; while ABKIN Indonesia emphasizes socio-cultural norms and national educational goals. Digital era challenges include digital data confidentiality, counsellors’ digital competence gaps, professional boundaries on social media, digital informed consent, and cross-border counseling. International associations have updated their ethical codes to include specific digital counseling regulations, yet Indonesia lacks comprehensive chapters on cyber counseling. Indonesian ethical codes, ABKIN, need to revise its ethical codes by adding chapters on cyber counseling, strengthening enforcement mechanisms, and integrating digital ethics into counselor education curricula.